Desenvolvimento de sistema de liberação continuada de capsaicina a partir de biomaterial natural para tratamento da dor neuropática - Santos, Marcelo Affonso dos (2024)
Rationale: Neuropathic pain, originating from dysfunctions in the peripheral or central nervous system, poses a challenge to medical practice. Faced with the limitations of conventional treatments, research in biomaterials for controlled release of analgesics and anti-inflammatories emerges as promising. This study focuses on the complexation of nano clays, such as montmorillonite, Cloisite Na+, and Cloisite 30B, with capsaicin (CAP), aiming at their potential use in patients with neuropathic pain. Nano clays, notably montmorillonite, demonstrate remarkable efficacy in sustained drug release and the expression of anti-inflammatory properties. The drug-clay complexation plays a crucial role in this context, conferring significant therapeutic potential, especially in the treatment of neuropathic pain. The choice of capsaicin, known for its anesthetic properties, strengthens this approach. Objective: To perform and evaluate the complexation of nano clays and capsaicin for the treatment of patients with diabetic neuropathy. Methods: Using analytical techniques such as Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetry (TG), and Differential Scanning Calorimetry (DSC), the complexed clays were characterized. CAP release assays were conducted to assess the efficiency of the substance release process. The selection of the most suitable clay was determined based on the results of these assays. Results: Preliminary results indicate successful drug-clay complexation of Cloisite 30B and Cloisite Na+, evidenced by FTIR, TG, and DSC, which showed different bands, degradation rates, and modified melting peaks, respectively. Cloisite Na+ stands out in CAP incorporation, justifying its selection for ongoing clinical trials in diabetic patients suffering from neuropathic pain